2015
DOI: 10.1042/bsr20150175
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal-mediated oligomerization of DnaA drives the occupancy-dependent rejuvenation of the protein on the membrane

Abstract: Initiation of DNA replication in bacteria requires recharging of DnaA with ATP. We demonstrate in the present study that this process involves the N-terminal domain-mediated oligomerization of the protein on the membrane, which can be modelled as a surface density-driven phase transition switch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Another possible mechanism of suppression could rely on the altered membrane properties in the metabolic mutants. The DnaA protein binds to the membrane, and the membrane phospholipids stimulate rejuvenation of DnaA-ATP [ 18 , 76 ]. Moreover, expression of genes related to the membrane synthesis was affected in the dnaA46 mutant at the restrictive temperature [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism of suppression could rely on the altered membrane properties in the metabolic mutants. The DnaA protein binds to the membrane, and the membrane phospholipids stimulate rejuvenation of DnaA-ATP [ 18 , 76 ]. Moreover, expression of genes related to the membrane synthesis was affected in the dnaA46 mutant at the restrictive temperature [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of the arrows indicate the approximate relative contributions of the different elements to the interconversion of the different forms. Stipled arrow: the relative contribution of phospholipid mediated nucleotide exchange (Sekimizu and Kornberg, 1988 ; Aranovich et al, 2006 , 2015 ) is unknown. RIDA: Replicative inactivation of DnaA (Katayama et al, 1998 ; Kato and Katayama, 2001 ); DDAH: datA dependent ATP hydrolysis (Kasho and Katayama, 2013 ); DARS: DnaA Reactivating sequence (Fujimitsu et al, 2009 ).…”
Section: Recent Additional Features Of Regulation Of Initiation By Dnmentioning
confidence: 99%
“…In particular, DnaA mutated at Asn44 or lysine 54 (Lys54) located on helix α3 is insensitive to RIDA in vitro and in vivo [ 31 ]. Interestingly, E. coli domain I has also been proposed to participate in the transition of DnaA-ADP into DnaA-ATP, which is able to initiate replication [ 62 ]. Such an exchange of nucleotides, called rejuvenation, is promoted by the interaction between DnaA domain III and acidic phospholipids in the cell membrane [ 61 ].…”
Section: N-terminus Of Bacterial Dnaamentioning
confidence: 99%
“…Such an exchange of nucleotides, called rejuvenation, is promoted by the interaction between DnaA domain III and acidic phospholipids in the cell membrane [ 61 ]. However, it has recently been demonstrated that this process strongly depends on DnaA protein membrane occupancy, which affects the functional state of DnaA [ 62 , 63 ]. It was proposed that domain I is particularly important for rejuvenation associated with DnaA density-driven, cooperative oligomerization [ 62 ].…”
Section: N-terminus Of Bacterial Dnaamentioning
confidence: 99%
See 1 more Smart Citation